The metahistory of Daniel Andreyev: at the intersection of philosophy, art and myth - Aleksandrov, Vladimir L. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes the concept of the Russian poet and thinker of the twentieth century, Daniеl Andreyev. Particular attention is paid to the basic notion of the concept – «metahistory». Reveals ontological and epistemological meaning of its . In a first aspect metahistory is understood as a complex of processes in the other (parallel) layers of the Earth, in the second – as the study of these processes, including three stages: metahistorical afflatus, contemplation and comprehension. It is stated that thanks metahistorical method of knowledge D. Andreyev was able, firstly, deeply analyzes the Russian and world history, and secondly, to give precise predictions about the most important events and processes of the second half of the twentieth century: the collapse of the Soviet Union and the socialist camp, the union of Europe. Particularly D. Andreyev’s mythmaking analyzes as a continuation of sophiology, trend of Russian religious philosophy. The author concludes that, despite the irrational, mystical character, the concept of D. Andreyev has great epistemological value and can be efficiently used in the study of current social, political and cultural processes, particularly globalization.